MITOS PEREMPUAN DAN PENERIMAAN DIRI DALAM ALBUM UNTUK DUNIA, CINTA, DAN KOTORNYA KARYA NADIN AMIZAH (FEMALE MYTHS AND SELF-ACCEPTANCE IN THE ALBUM UNTUK DUNIA, CINTA, DAN KOTORNYA BY NADIN AMIZAH) - Pualilin, Leony Indaryani; Nurmalisa, Dina (Universitas Lambung Mangkurat, 2025)
AbstractFemale Myths and Self-Acceptance in the Album Untuk Dunia, Cinta, Dan Kotornya by Nadin Amizah. This research examines the mythical representation of women and self-acceptance in the lyrics of the album